Improving Skills in Batik Design through Digital Application for a Pesantren Community in Jombang - Mas'udah, Kusuma Wardhani; Issafira, Radissa Dzaky; Fauziyah, Nur Aini; Hidayah, Euis Nurul (UI Scholars Hub, 2022)
This community engagement aims to improve skills in batik design through digital applications. Islamic boarding school or also known as pesantren is Indonesia’s oldest religious educational institution. Along with rapid industry advancements, such a school is expected to follow the development by creating innovations with commercial and representative value. Based on this motivation, a training program on design software and blog-based online publishing tools for beginners is given to the students in Babussalam Pesantren, Jombang Regency, Indonesia. The idea of batik is discussed in this article as a part of the entrepreneurial knowledge and skill at the pesantren, preparing the students for future entrepreneurship. This community project consists of two kinds of training—(1) designing batik with an innovative and contemporary pattern using a software application such as CorelDRAW and (2) designing and commercializing the batik product using free publishing online platforms such as Blogger or Blogspot, as the widely known domain. The participants are 28 high school students aged 16–18 years old, including 14 male and 14 female students. To observe the process of learning, pre- and post-questionnaires were conducted. The results show that 84% and 89% of students have not used CorelDRAW and blog-based media before, respectively. However, after the training, the students show enthusiasm, with 73% expressing interest and 63% wanting to deepen their knowledge of CorelDRAW design. Furthermore, 27% of students show interest in blog design and 37% want to learn further. Hopefully, with this entrepreneurship training, pesantren students are ready and confidently enter the business community.